HEALTH RETREAT BERNUANSA SLOW LIVING ECO-TROPICAL SOLUSI UNTUK KAUM URBAN - Dewa Ayu Putu Ratih Permata Putri; Ngurah Gede Dwi Mahadipta; I Putu Gede Suyoga (LPPM Institut Desain dan Bisnis Bali, 2019)
At this time, a health retreat for urbanities is needed. Health retreat is a facilities of resigning from the hectic daily activities of urban people and to keep them away from the noise of the urban environment, so the complaints that are urban people feel such as sress, tiredness, and poor diet will get the solution when they participating in health retreat acrivities. Urban people is people who livw in urban area with various kind of activities, such as office employees, students, entepreneurs. Many urban people complaint about their lifestyle that less haelthy, because of their hectic activities, until many urban people are stressed. Several stress trigger factor in urban people inclued the noise environment factor, and then traffic jams, pollution, food with less nutrition, and lack of consciouness of the importance activities. The location of this research is in Ubud. The research methods is use method of collecting data with observation, interviews and documentation. The data sources consists of journals and books. The data analysis phase is conducted using qualitative and quantitative methodes, presentation, and accumulation of conclusions. The result of analysis are then carried out a proses of synthesis prosess so as to produce design criteria that must be completed in the transformation process. Research on the design of the health retreat facilities, it aims to know the need for health retreat facilities for urban communities and wants to understand the application of slow living eco-tropical themes and concepts to the design of health retreat facilities and solutions to problems proposed by urbanites.